History and Civilization of the Modern Era - Ifkar Rasyid; Imamul Muttaqin (Tarikhuna: Journal of History and History Education, 2022)
The history of Islamic civilization has experienced ups and downs in each period. The Islamic world achieved glory and progress in the classical era from the 7th to the 9th centuries AD. Advancements in philosophy, science, technology, architecture, and the arts successfully positioned Islam as a leading civilization in the world. However, indications of decline that began to appear in the medieval period brought complex problems to Islam as it entered the modern era. Intellectual stagnation, coupled with other factors, led to Islam losing its dominance. In this paper, the history of Islamic civilization in the modern era will be formulated in three discussions: 1) the decline of Islam and the progress of the Western world; 2) the Islamic world and Western imperialism; 3) social movements and struggles for independence in the Islamic world.